2020
DOI: 10.1371/journal.pone.0234760
|View full text |Cite
|
Sign up to set email alerts
|

PeskAAS: A near-real-time, open-source monitoring and analytics system for small-scale fisheries

Abstract: Small-scale fisheries are responsible for landing half of the world’s fish catch, yet there are very sparse data on these fishing activities and associated fisheries production in time and space. Fisheries-dependent data underpin scientific guidance of management and conservation of fisheries systems, but it is inherently difficult to generate robust and comprehensive data for small-scale fisheries, particularly given their dispersed and diverse nature. In tackling this challenge, we use open source software c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 18 publications
(20 reference statements)
0
14
0
Order By: Relevance
“…If well, we addressed only a part of the complexity associated with the SSF using the RF model to classify fishing and transit positions of vessels, it is still necessary to increase the number of trips with onboard observers to improve the analytical forecasting capacity of the approach used in this study. Lastly, it is important to indicate that from the pilot VMS data, we could not infer which species were caught or the fishing gear used; thus, incorporation of these data could help to analyze such relationships (fishing gears-target species) and add more detail to differentiate the potential fishing grounds according to different target species (e.g., D'Andrea et al, 2020;Tilley et al, 2020). Despite the limitations in our study, our results showed the usefulness of VMS for SSF to help understand the fleet dynamics and provided insights into the potential fishing grounds available in the SGoM region for the first time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If well, we addressed only a part of the complexity associated with the SSF using the RF model to classify fishing and transit positions of vessels, it is still necessary to increase the number of trips with onboard observers to improve the analytical forecasting capacity of the approach used in this study. Lastly, it is important to indicate that from the pilot VMS data, we could not infer which species were caught or the fishing gear used; thus, incorporation of these data could help to analyze such relationships (fishing gears-target species) and add more detail to differentiate the potential fishing grounds according to different target species (e.g., D'Andrea et al, 2020;Tilley et al, 2020). Despite the limitations in our study, our results showed the usefulness of VMS for SSF to help understand the fleet dynamics and provided insights into the potential fishing grounds available in the SGoM region for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, the implementation of a VMS in the region is challenging, from gaining the acceptance of fishers to issue of the costs involved in the implementation of the system and its maintenance, especially given the size of the fleet (in the region there are around 20,000 small-scale vessels; Coronado et al, 2020). Thereby, a VMS for SSF demands the development of a cost-effective platform for daily catch recording in an integrative way, including the type of gears and species captured whenever possible (e.g., D'Andrea et al, 2020;Tilley et al, 2020). This type of data could be coupled with that obtained from onboard observers, and a program of monitoring systems in the coast, thus the acquisition of explicit spatial data from the smallscale vessels (Russo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in Bobonaro municipality or Amblygaster spp. in Dili-but not 'herring' from the 'Elopidae family, ' as currently recorded (Tilley et al, 2020;WorldFish and MAF, 2021). We cannot provide any insight on where this name may relate to fusiliers or oxeye herring.…”
Section: Considerations For Fisheries Monitoring and Management And Future Research Needsmentioning
confidence: 91%
“…Furthermore, Timorese common names listed on FishBase also include similar name 'kopi' for fusiliers of the Caesionidae family, as well as for Tropical Pilchard A. sirm (Froese and Pauly, 2020). National fisheries monitoring in Timor-Leste currently records landings at the family level due to the difficulties associated with accurately identifying mixed-species catches to species level across the country (Tilley et al, 2020). However, this example illustrates that the same or similar local name could relate to three different families.…”
Section: Considerations For Fisheries Monitoring and Management And Future Research Needsmentioning
confidence: 99%